Martes americana - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Martes americana (Turton, 1806). A Gen. Syst. of Nat., 1:60. TYPE LOCALITY: E. North America. DISTRIBUTION: Alaska and Canada south to N. California, south in the Sierra Nevada and Rocky Mtns, to 35° N. COMMENT: May be conspecific with martes, melampus, and zibellina; see Anderson, 1970, Acta Zool. Fenn., 130: 132; Hagmeier, 1961, Can. Field Nat., 75: 122- 138; and Corbet, 1978: 172; but see also Hall, 1981:981; Gromov and Baranova, 1981:256- 258. ISIS NUMBER: 5301412004006001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 259, DOI: 10.5281/zenodo.7352980